PELATIHAN PEMBUATAN ECO ENZYME SEBAGAI ALTERNATIF PENGELOLAAN SAMPAH ORGANIK DI KOTA BATU - Vian Eka Putra; Rizky Fadila; Dyan Lindawati; Jatu Permana Gupitasari; Erisa Ariya Andayani; Yhen Ari Bekti (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2022)
This community service activity aims to obtain alternative natural products as cleaning fluids, disinfectants, and organic fertilizers as well as reduce the impact of environmental pollution due to the accumulation of organic waste. The implementation method begins through the preparation, pre-test, training and post-test stages. Evaluation is carried out on the process which includes the attendance, enthusiasm, and responses of participants to the training activities, as well as to the eco-enzyme products produced by the participants. The results of the service show that the training activities have been able to improve the knowledge and skills of the community in processing organic waste into eco-enzymes. The results of the evaluation showed that the response, enthusiasm, acceptance, presence and participation of the community in training activities were very good. The eco-enzyme products produced by the participants met several indicators, namely brownish color, distinctive fruity odor with a slight alcohol aroma, acidic pH (3-4), and not overgrown with fungus or maggots.